DAMPAK PERUBAHAN KURIKULUM MERDEKA DAN KESIAPAN TENAGA PENDIDIK TERHADAP PENYESUAIAN PEMBELAJARAN DI SEKOLAH - Agung Hartoyo; Rima Melati; Martono Martono (STKIP Persada Khatulistiwa Sintang, 2023)
Changes to the curriculum are a necessity to keep up with developments so that the quality of education improves. The Ministry of Education, Culture, Research and Technology (Kemendikbudristek) has issued a policy to implement the kurikulum Merdeka. The Kurikulum Merdeka is a new policy created to improve the education system and quality in Indonesia. By implementing the kurikulum merdeka, it is hoped that it will be able to have a positive impact on students, namely knowledge, skills and character, thereby producing students who are intelligent, skilled and have good ethics. This research was carried out in the form of a literature study, with data sources in the form of research articles and books. The results of the study show that, apart from students, teachers experience a very pronounced impact, especially their readiness to teach. It is hoped that the implementation of this kurikulum merdeka will inspire the next generation to continue to improve themselves to improve quality and competitiveness in the world of education. The implementation of this kurikulum merdeka is a tool for us to achieve better results and compete in the world of national and international education.